2018
DOI: 10.1021/acs.langmuir.7b04182
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Events in Oligo(3-methoxythiophene) Coating Solutions and Their Effect on the Goldlike Coating Film Properties

Abstract: Metal-free, metal-like lustrous films may find applications in a variety of fields, and a study of the factors affecting their stability is highly desirable. In particular, chemical events occurring in the coating solutions might affect the supramolecular organization of the films and therefore the metal-like luster. Herein, the chemical events occurring in acetonitrile and nitromethane coating solutions of oligo(3-methoxythiophene) and their effect on the optical properties of the films were investigated by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…The differences in color between films 1 and 2 can be attributed to differences in the effective conjugation lengths of oligomers 1 and 2 (see Figure S6, Supporting Information). Focusing on the maximum reflectance, the reflectance of both films 1 and 2 (28 and 40%, respectively) significantly exceeds the reflectance of film 3 (18%), , also exceeding that of previously reported metal-free organic gloss films or aggregates (11–22%). Also, the excellent reflectance of both films 1 and 2 is comparable to the reflectance of coating films cured from metal-effect pigments. , …”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…The differences in color between films 1 and 2 can be attributed to differences in the effective conjugation lengths of oligomers 1 and 2 (see Figure S6, Supporting Information). Focusing on the maximum reflectance, the reflectance of both films 1 and 2 (28 and 40%, respectively) significantly exceeds the reflectance of film 3 (18%), , also exceeding that of previously reported metal-free organic gloss films or aggregates (11–22%). Also, the excellent reflectance of both films 1 and 2 is comparable to the reflectance of coating films cured from metal-effect pigments. , …”
Section: Resultsmentioning
confidence: 55%
“…To find the cause of the high luster property, we conducted specular reflectance measurements, color measurements, ellipsometry measurements, and surface roughness measurements on both films 1 and 2. The specular reflection spectra of films 1 and 2 are shown in Figure a; the spectrum , of film 3 and both evaporated metallic gold and copper films (200 nm thick) are also shown for comparison (Figure b). Films 1 and 3 strongly reflected yellow light (570–590 nm), orange light (590–620 nm), and red light (620–750 nm) yet only slightly reflected green light (495–570 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, conventional metallic luster paints contain metal flakes, such as aluminum and zinc, which often pollute the environment. To overcome these problems, attention has been directed to the preparation of metallic luster materials using metal-free organic compounds. The fabrication of metallic luster materials has been reported using various organic compounds, including thiophene, pyrrole, aniline, porphyrin, and thiadiazol derivatives . One of the present authors has also reported the preparation of metallic luster materials using azobenzene derivatives.…”
Section: Introductionmentioning
confidence: 83%